The Relationship between Social Media and Academic Performance: Facebook Perspective - Mazuri, Abd Ghani; Ibrahiem Mohammed, Habes Ahamed; Alghizzawi Mahmoud, Zeyad Mohammad; Rifat, Khalaf (2018)
The aim of this paper is to highlight the impact of social media on students in the higher educational universities and its impact on the students’ academic performance. Social media has become one of the most popular means of communication due to its ability to deepen the conviction of the recipient and to increase his knowledge and trends. The study focuses on the researchers’ observation and follow-up of these sites; the impact of these sites on the audience by relying on Facebook applications in the Middle East and the world. The researchers employed a comparative and experimental approach to measure the impact of Facebook and providing the results by relying on the recommendations and outputs concluded by scientific studies published in refereed journals. The study indicated that a large number of university students are using social media with more focus on Facebook, which in turn negatively affect their academic results.